Neonatal Outcome of Antenatal Mothers with Pregnancy Induced Hypertension in Antenatal Ward of Kathmandu Medical College and Teaching Hospital - Shrestha Pradhan, Santoshi; Paudel, Sabitra; Parajuli, Puspa; Rana Khagi, Bina (Birat Journal of Health Sciences, 2018)
Introduction: Hypertensive disorders seem to complicated in approximately 5-15% of pregnancies. Pregnancy induced hypertension (PIH) increases the risk of maternal and perinatal morbidity and mortality.Objective: To assess the neonatal outcome and to identify the association between the demographic variables and outcome of Pregnancy Induced Hypertension in antenatal ward of Kathmandu Medical College and Teaching Hospital.Methodology: Prospective study design was conducted for the study in Obstetrics ward of Kathmandu Medical College Teaching Hospital. The population was the 100 antenatal mothers with pregnancy induced hypertension admitted in antenatal ward and purposive convenient sampling technique was used to collect the data. The structured questionnaire was designed and the data was collected through interview technique from 1st February 2014 to 10 March 2016. The collected data was analyzed using SPSS programme.Results: Regarding neonatal outcome the findings of the study showed that most of the babies 83% had normal weight. The most of the babies 82% had adequate for gestational age. Regarding Apgar score half of the babies 50% scored mild asphyxia at the first minute whereas most of the babies 93% scored no asphyxia at five minutes after delivery. Regarding perinatal outcome 13% babies were delivered premature, 7% had birth asphyxia, 5% were born with low birth weight and stillbirth whereas only 1% had early neonatal death. The present study revealed that there was significant association between gestational age of delivery and Apgar score at 5 minutes and there was significant association between age and perinatal management outcome, gestational age of delivery and perinatal morbidity management, grading of proteinuria and perinatal morbidity management, grading of oedema and perinatal management outcome regarding neonatal outcome of pregnancy induced hypertension.Conclusion: Pregnancy induced hypertension during pregnancy were associated with a higher risk of adverse neonatal outcomes. Women with pregnancy induced hypertension during pregnancy had a higher risk of emergency caesarean section, pre-term birth, neonatal death, low birth weight children and neonates with low Apgar score. Maternal and fetal morbidity and mortality can be reduced by early recognition and institutional management.Birat Journal of Health SciencesVol.2/No.3/Issue 4/Sep- Dec 2017, Page: 255-259